(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
This study was designed to find out the relationship between uses of different contraceptives and the prevalence of vaginal candidiasis. High vaginal swabs were obtained from 350 women in the age group of 15-45 years with vaginal discharge attending at Sir Salimullah Medical College Hospital, Dhaka, which comprised of 247 contraceptive users & 103 non-contraceptive users. A detailed clinical history and a thorough examination of all the cases were done. After making the clinical diagnosis, appropriate tests for diagnosing Candidiasis were done by using standard procedures. Of the 247 women of contraceptive users, Candida species was isolated in 140 (56.7%) cases compared to 32 (31.1%) from 103 non-contraceptive users (p value <0.001). Different species of Candida were isolated from 172 (49.1%) cases among 350 women of which C. albicans was found in 125 (72.7%) cases, C. glabrata in 29 (16.9%) cases, C. tropicalis in 13 (7.5%), and C. krusei in 5 (2.9%) cases. Among 173 oral contraceptive users, the isolation rate of Candida species was 120 (69.4%). This was followed by injectables (17, 12.2%) and IUCD (03, 2.1%) cases (p value <0.05). The study revealed a strong association between use of contraceptives and the prevalence of vaginal infection by Candida species of which C. albicans was the most common species (72.7%). Among all contraceptives, use of oral contraceptive pills (OCP) was found as the most common cause of vaginitis, next to which were injectables and IUCDs. Bangladesh J Med Microbiol 2007; 01 (02): 61-64